Treatment of painful hypertrophic osteoarthropathy associated with non-small cell lung cancer with octreotide: a case report and review of the literature. Issue 2 (7th August 2011) - Birch, Elizabeth; Jenkins, Debbie; Noble, Simon
Abstract : Hypertrophic osteoarthropathy (HOA) is a syndrome most commonly associated with non-small cell lung cancer and consists of periostitis, digital clubbing and painful polyarthropathy. Its symptoms may be disabling and are reportedly difficult to manage effectively with conventional analgesia. We present a case of a lung cancer patient with opioid resistant painful HOA in whom analgesia was achieved with octreotide.